Estímulos relacionados a satisfacción laboral de enfermería en un hospital de segundo nivel de atención - Sánchez González, Javier (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Job satisfaction determines the adequate performance of people in their work, the stimuli will cause a response in the human being and it may be that they are associated. Aim. To analyze the relationship of stimuli with job satisfaction in the nursing staff of a second level care hospital in the State of Mexico. Methodology. Quantitative, non-experimental, correlational and cross-sectional study. Probabilistic sample with 95% reliability and 5% errors, a total of 123 participants selected with simple random sampling. Two instruments were used: Stimuli (α= 0.940), the higher the score, the greater the stimuli or high level of stress, and Job satisfaction (α= 0.722), the higher the score, the higher the job satisfaction. All nursing staff were included, trust contracts and those who did not agree to participate were excluded. It was analyzed through the SPSS version 25 software. Results. 82% were women, according to the type of position, 56% have a contract and 73% are nursing graduates. In relation to stimuli, 50% reported it as low and 90% with average job satisfaction. No statistically significant relationship was found between the variables (p>.05). Conclusion. Although there was no relationship between stimuli and job satisfaction, the factors that most affected job satisfaction were: lack of learning opportunities, lack of job recognition, poor infrastructure, interpersonal conflicts, and low wages. The identification of these factors is important to base improvements. that affect the quality of care.

La satisfacción laboral va a determinar el adecuado desempeño de las personas en su trabajo; los estímulos provocan una respuesta positiva o negativa en el ser humano, los cuales pueden ser que estén asociados. Objetivo. Analizar la relación de los estímulos con la satisfacción laboral en el personal de enfermería de un hospital de segundo nivel de atención del Estado de México. Metodología. Estudio cuantitativo, correlacional y transversal. Muestreo probabilístico, aleatorio simple. Muestra conformada por 123 participantes que cumplieron los criterios de selección de un hospital de segundo nivel en el Estado de México. Se utilizaron dos instrumentos: Estímulos (α= 0.940), a estímulos mayores, mayor nivel de estrés. Satisfacción laboral (α= 0.722), a mayor puntuación mayor satisfacción laboral. Los instrumentos de recolección de datos fueron auto aplicados. Se consideraron aspectos éticos y legales en investigación en humanos vigentes en México. Análisis estadístico a través del software SPSS versión 25. Resultados. 82% de participantes eran mujeres; de acuerdo al tipo de plaza 56% cuentan con contrato y 73% eran licenciados en enfermería. El 50% presentó estímulos estresantes bajos; 90% con satisfacción laboral media. Conclusión. Se identificó que los participantes mostraron baja satisfacción laboral por la falta de oportunidades de aprendizaje y de reconocimiento laboral; inadecuada infraestructura, conflictos interpersonales y sueldos bajos, lo que condiciona en la baja calidad de los cuidados.
Facultad de Enfermería. Maestría en Enfermería
Keywords: info:eu-repo/classification/cti/3; FE-M-2023-1306; Gestión dirección y liderazgo; Satisfacción laboral; Estímulos; Profesionales de enfermería; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16727